DESIGN OF A MINI-SCALE CRYSTAL ICE SHAVING MACHINE AT CV. LEGUSA ICE KRISTAL, FIFTY-CITY DISTRICT USING SOLIDWORKS - Fauzan; Muchlisinalahuddin; Riza Muharni; Dytchia Septi Kesuma (Badan Penerbit Universitas Muria Kudus, 2026)
The crystal ice shaving process is one of the important stages in crystal ice production that affects the quality and efficiency of production, especially on a small scale business. In practice, the ice shaving machines used often have sizes that do not match the production capacity and are less efficient in energy consumption. These problems encourage the need to design a mini-scale crystal ice shaving machine that suits user needs. This study aims to design a mini-scale crystal ice shaving machine with a capacity of 5 kg/hour that has compact dimensions, is energy efficient, and is able to produce consistent ice shavings. The research method used is a machine design based on mechanical engineering calculations, including analysis of power requirements, transmission systems, machine elements, and modeling using SolidWorks software. The design results show that the machine with a 1 HP motor, a 14:1 pulley-belt transmission system, and a 250 mm diameter rotor is capable of producing a working rotation of 100 rpm with adequate torque. The resulting design is considered suitable for development to the manufacturing stage.